Correlation between Disease Duration, Disease Activity Scoreand Disability Score with Diastolic Dysfunction in RheumatoidArthritis Women in Dr. Cipto Mangunkusumo Hospital - Antono, Dono; Dhaki, Bernard Agus Sakti; Isbagio, Harry; Shatri, Hamzah (UI Scholars Hub, 2017)
Introduction. There are only few studies about correlation between non traditional risk factor and diastolic dysfunction in RA patients. This study aims to determinate the correlation between non traditional risk factors, including disease duration, disease activity and disability score with the diastolic dysfunction of women with RA. Methods. A cross-sectional, consecutive sampling study was conducted to 52 RA women without any previous cardiovascular disease history. All participants underwent an echocardiography to assess diastolic dysfunction and other findings associated. Duration of disease was assesed by direct interview, while the disease activity by calculating DAS28 and disability score by HAQ-DI. Results. Diastolic dysfunction was found in 30.8 % of study participants (13.5 % for each low and moderate grade, while severe was 3.8% ). Median duration of disease was 26.5 months (range 2-240), mean DAS28-CRP score was 2.69±1.11 while median DAS28-ESR score was 3.65 (range 1.13-7.5), and median HAQ-DI score was 0.29 (range 0-2.38). LV hypertrophy was found in 34.61% participants. Mean EF was 66.7±5.76%. Valve abnormality was found in 34.6% study participants. Correlation between duration of disease, DAS28-CRP, DAS28-ESR and HAQ-DI score with E/A in sequence was r= -0.065 (p=0.89), r=0.393 (p=0.38), r=0.357 (p=0.43), r=0.630 (p=0.12); while with E/E’ in sequence was r=0.136 (p=0.77), r= - 0.536 (p=0.21), r= - 0.393 (p=0.38), r=0.374 (p=0.41). Conclusions. Duration of the disease, disease activity score, and disability score in rheumatoid arthritis women had no correlation with diastolic dysfunction.